Assessment of satisfaction with hospital care in the ED and the Admissions depending on the place of living - Kos, Marek; Dziewa, Agnieszka; Drop, Bartłomiej (Polish Journal of Public Health, 2013)
Introduction. Patient satisfaction should be a key element in the functioning of any healthcare facility. Understanding and meeting the needs of the patient on the appropriate quality level can be a “to be or not to be” for the hospital. Aim. The aim of the study was to investigate patients’ views about patient satisfaction with medical care implemented in the emergency department and the admissions of the District Hospital in Kraśnik depending on their place of residence. Material and methods. Patients’ satisfaction survey was carried out in the following two years: in January 2012 and in February 2013. The study involved 95 respondents who completed the questionnaire individually, and in case when establishing contact with the patient was not possible, family members or carers made the assessment. A tool for research was a questionnaire called “Patient satisfaction survey” designed by the nursing managers and approved by the management of the hospital. Results. Respondents assessed the work of the Emergency Department (ED) and the Admissions well. In the first year of the study, 55.5% of patients rated the ED work very well, and the Admissions – well (58.1%). Patients living in rural areas assessed ED very well and well (45.5% each), and assessed the Admissions – well 48.4%. In the next year of the study, the patients living in the city gave good ratings both to the ED department and Admissions – 41.7% and 69.45% of the patients respectively, similarly as the patients from rural areas – 46.8% and 43.2% respectively. Conclusions. Overall rating of health services made by hospitalized patients and the availability, terms and conditions of the treatment course was very positive. The assessments of the ED and hospital Admissions were not affected by the patients’ place of residence.